Optimizing Service Valve Material Inventory Control: An Analysis Using ABC Approach, Croston Forecasting, and Economic Order Quantity in a Distribution Company - Salsabillah, Zakia; Santosa, Helmi Rizqi; Adi, Tri Warcono (Jurnal Logistik Indonesia, 2025)
This study aims to optimize the maintenance of service valve material inventory at PT. X, a company providing, repairing, and manufacturing equipment for the oil and gas industry in Indonesia. The problem faced by the company is the imbalance between inventory levels and actual demand, especially for critical components such as service valve materials that have an intermittent demand pattern. The research method integrates three approaches, namely the ABC classification to group materials based on annual consumption value, the Croston method to predict intermittent demand, and the Economic Order Quantity (EOQ) to determine optimal procurement policies. The results of the study identified 6 types of service valve materials included in category A (75% of total consumption value) from 612 types of materials. The implementation of the Croston method proved effective in predicting intermittent demand, while the application of EOQ based on forecasting results resulted in optimal procurement policies including optimal order quantity, annual order frequency, safety stock, and reorder point. The integration of these three methods provides a total savings of Rp657,152,210.44 or approximately 10.51% of the total inventory costs of category A service valve materials, with savings ranging from 9.35% to 11.52% for each material, thus significantly increasing cost efficiency and optimizing inventory management.